Disulfonimide-Catalyzed Asymmetric Synthesis of δ-Amino-β-Keto Esters - Wang, Qinggang; List, Benjamin (Synlett, 2015)
A chiral disulfonimide-catalyzed asymmetric synthesis of δ-amino-β-keto esters via a vinylogous Mukaiyama–Mannich reaction of the Chan diene with N-Boc imines has been developed. The desired products were obtained in good to excellent yields and enantioselectivities.
Keywords: chiral disulfonimides; δ-amino-β-keto esters; Chan diene; N-Boc imines; vinylogous Mukaiyama–Mannich reaction